2020
DOI: 10.1002/jsfa.10554
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus2016SWU.05.0601 regulates immune balance in ovalbumin‐sensitized mice by modulating expression of the immune‐related transcription factors and gut microbiota

Abstract: BACKGROUND Probiotics regulate host immune balance, which may reduce immune‐related diseases. The effects and mechanisms of Lactobacillus rhamnosus 2016SWU.05.0601 (Lr‐0601) on the immune response in ovalbumin (OVA)‐sensitized mice were explored. RESULTS Lr‐0601 reduced serum immunoglobulin (Ig)E and OVA‐IgE and attenuated the alteration in lung pathology in OVA‐sensitized mice. Lr‐0601 blocked OVA‐induced up‐regulation in serum T helper (Th) 2 and Th17 cytokines but increased the serum levels of Th1 and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Oral administration of probiotic strains such as Lactobacillus and Bifidobacterium alleviated weight loss and reduced the levels of serum OVA-sIgE, intestinal Th2-type, and Th17-type cytokines. 24,25 The research is now focusing on the specific mechanism how probiotic strains alleviated FA. Probiotic strains could alleviate FA pathological symptoms by regulating the functionality of DC.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of probiotic strains such as Lactobacillus and Bifidobacterium alleviated weight loss and reduced the levels of serum OVA-sIgE, intestinal Th2-type, and Th17-type cytokines. 24,25 The research is now focusing on the specific mechanism how probiotic strains alleviated FA. Probiotic strains could alleviate FA pathological symptoms by regulating the functionality of DC.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis encompassing 17 studies, probiotics may significantly lower the risk of infantile eczema, thus suggesting a new potential indication for probiotic use in pregnancy and infancy ( Zuccotti et al, 2015 ). Recently, L. rhamnosus Lr-0601 proved to be able to modulate the balance of Th1/Th2 and Treg/Th17 in ovalbumin-sensitized mice ( Song et al, 2020 ). In mouse model with FA induced by ovalbumin, Li N. et al (2020) observed an abnormal gut bacterial composition, accompanied by increased immunoglobulin G, immunoglobulin E, and interleukin-4/interferon-gamma.…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…Administration of C. butyricum CGMCC0313-1 significantly elevated sIgA and Foxp3 + Treg cells in the spleen in mice with β-lactoglobulin (BLG) sensitivity and markedly reduced anaphylactic symptoms [109]. L. rhamnosus 2016SWU.05.0601 has recently been demonstrated by Song et al to modulate the expression of immune-related transcription factors and gut microbiota, consequently regulating the imbalance of Th1/Th2 and Treg/Th17 in OVA-sensitized mice [110]. Treatment with a probiotics mixture (L. lactis KF140, Pediococcus pentosaceus KF159, L. pentosus KF340, L. paracasei 698, and Bacillus amyloliquefaciens 26N) significantly suppressed the OVA-induced allergic symptoms, inhibited the release of IgE and Th2 cytokines, and promoted the development of Foxp3 + Tregs in mice [111].…”
Section: Gut Microbiota Manipulation For the Prevention And Treatment...mentioning
confidence: 97%